An octane mediated strategy towards Ti-containing HMS-type mesoporous materials incorporated with methyl for high-efficiency oxidative desulfurization. (15th November 2020) - Wei, Yue; Li, Gang; Yi, Yanhui; Liu, Jiaxu; Guo, Hongchen
Graphical abstract: Highlights: Methyl-incorporated C1-HMS-x has been synthesized via n-octane-mediated strategy. Desirable porosity is attained due to the synergy of n-octane and organosilane. C1-HMS-x shows high-efficiency solvent-free and Pickering emulsion-assisted ODS. The catalyst could adsorb oxidized sulfur compounds and boost the ODS process. Abstract: Delicate mediation on structural properties and surface wettability of catalysts is the key strategy towards a high catalytic performance but remains challenging. Herein, organic–inorganic hybrid Ti-containing mesoporous materials uniformly incorporated with methyl (C1-HMS-x) have been successfully fabricated by an in situ n-octane mediated strategy and used as catalysts in solvent-free oxidation desulfurization (ODS) with H2 O2 . Benefiting from the synergy of n-octane with organosilane, the C1-HMS-x showed more tetrahedrally coordinated Ti sites, remarkably increased specific surface area and pore volume. Such properties endow the catalyst with not only a higher intrinsic catalytic activity, but also excellent amphiphilicity and facilitated mass transfer. Besides, the catalyst also acts as a high-efficiency adsorbent for oxidized sulfur compounds, further boosting the ODS process. As a result, complete desulfurization of model oil containing 500 ppm dibenzothiophene (DBT) was achieved with a low ratio of O/S as 2.5 and catalyst dosage as 5 g/L. The C1-HMS-x also presented greatly enhanced desulfurization efficiency for refractory thiophene (Tp) and steric hindered 4, 6-dimethyldibenzothiophene (4, 6-DMDBT). More importantly, the mediation of morphology and wettability by n-octane enables the generated catalyst to be a superior Pickering interfacial catalyst for ODS without stirring. A higher ODS conversion was achieved in the oil-in-methanol emulsion system than that in methanol-in-oil system. The easier accessibility of active sites at emulsion interface for S-compound is responsible for the enhanced emulsion catalytic performance. Such mediation strategy and new catalytic system hold a great promise for next-generation green and sustainable chemistry.